2017
DOI: 10.1209/0295-5075/117/28004
|View full text |Cite
|
Sign up to set email alerts
|

Stall force of a cargo driven by N interacting motor proteins

Abstract: We study a generic one-dimensional model for an intracellular cargo driven by N motor proteins against an external applied force. The model includes motor-cargo and motormotor interactions. The cargo motion is described by an over-damped Langevin equation, while motor dynamics is specified by hopping rates which follow a local detailed balance condition with respect to change in energy per hopping event. Based on this model, we show that the stall force, the mean external force corresponding to zero mean cargo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Using models similar to ours, but with discrete steps rather than continuous motor dynamics [25,28], found a similar monotonic and concave functional dependence of the mean velocity v on motor number N, although their findings are restricted to relatively small N. Likewise, [28] also found D eff ∝ 1/N for the greatest N they investigated. Another recent study [29] found that the total load capacity, or effective stall force, is N times the stall force for a single motor. We can easily incorporate into our model a constant external force f ext pulling the cargo in the opposite direction of the chemical force driving the motors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using models similar to ours, but with discrete steps rather than continuous motor dynamics [25,28], found a similar monotonic and concave functional dependence of the mean velocity v on motor number N, although their findings are restricted to relatively small N. Likewise, [28] also found D eff ∝ 1/N for the greatest N they investigated. Another recent study [29] found that the total load capacity, or effective stall force, is N times the stall force for a single motor. We can easily incorporate into our model a constant external force f ext pulling the cargo in the opposite direction of the chemical force driving the motors.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of transport by single motors has shown that pulling a diffusing cargo and pulling against a constant force lead to qualitatively different transport behavior [23,24]. Researchers have proposed and explored several dynamical models for transport of diffusive cargo by multiple motors [25][26][27][28][29][30]. These approaches rely primarily on numerical simulation, and as such are limited by computational resources to exploring systems with relatively small numbers of motors.…”
Section: Introductionmentioning
confidence: 99%
“…Using models similar to ours, but with discrete steps rather than continuous motor dynamics, [24] and [27] found a similar monotonic and concave functional dependence of the mean velocity v on motor number N , although their findings are restricted to relatively small N . Another recent study [28] found that the total load capacity, or effective stall force, is N times the stall force for a single motor. We can easily incorporate into our model a constant external force f ext pulling the cargo in the opposite direction of the chemical force driving the motors.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of transport by single motors has shown that pulling a diffusing cargo and pulling against a constant force lead to qualitatively different transport behavior [23]. Researchers have proposed and explored several dynamical models for transport of diffusive cargo by multiple motors [24][25][26][27][28][29]. These approaches rely primarily on numerical simulation, and as such are limited by computational resources to exploring systems with relatively small numbers of motors.…”
Section: Introductionmentioning
confidence: 99%
“…Many specific models of transport systems have been explored, including deterministic phenomenological models [7,9,10], discrete stochastic models [11][12][13], and continuous stochastic models [14,15]. A common goal of these investigations has been to determine how various parameters (such as coupling strength, stall force, diffusivity, and number of motors) tune the performance of these systems.…”
mentioning
confidence: 99%